2008
DOI: 10.1007/s11524-008-9307-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sentinel Surveillance and Geographic Information Systems to Monitor Trends in HIV Prevalence, Incidence, and Related Risk Behavior among Women Undergoing Syphilis Screening in a Jail Setting

Abstract: Innovative methods are needed to systematically track the HIV epidemic and appropriately target prevention and care programs in vulnerable populations of women. We conducted sentinel surveillance among women entering the jail system of San Francisco from 1999 to 2001 to track trends in HIV incidence, HIV prevalence, and related risk behavior. Using geographic information software (GIS), we triangulated findings to examine the spatial distribution of risk and disease. A total of 1,577 female arrestees voluntari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Three HIV incidence studies among incarcerated individuals were identified (Table 7) (61–63) with a pooled total of 5168 participants and 2891.5 person‐years of follow‐up. Incidence estimates ranged from 0 to 0.5 per 100 person‐years, and the pooled incidence was 0.4 per 100 person‐years (95% CI 0.2–0.7, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Three HIV incidence studies among incarcerated individuals were identified (Table 7) (61–63) with a pooled total of 5168 participants and 2891.5 person‐years of follow‐up. Incidence estimates ranged from 0 to 0.5 per 100 person‐years, and the pooled incidence was 0.4 per 100 person‐years (95% CI 0.2–0.7, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…And other studies done by Bellad et al .,[ 4 ] among the inmates of central jail; Belgaum showed that 13% of the inmates suffered from diarrhea, followed by pulmonary TB and HIV contributed 2% and 1.5% respectively. Andrea et al .,[ 9 ] in San Francisco country jail has showed HIV prevalence was 1.8%. Baillargeon et al .,[ 10 ] in Texas prison showed that infectious diseases (29.6%) constituted the most prevalent major disease category among inmates.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of diseases having been monitored in both developed countries (Canada [ 69 ], France [ 70 ], US [ 71 , 72 ], the Netherlands [ 73 ]), and developing ones (South Africa [ 74 ], Nicaragua [ 75 ], India [ 76 ], Vanuatu [ 77 ], Congo [ 78 ], Trinidad and Tobago [ 79 ]) using GIS include injury [ 74 ], respiratory and acute gastrointestinal illness [ 71 ], HIV/AIDS [ 72 , 73 , 76 , 78 ], malaria [ 77 , 80 ], rabies epidemic [ 79 ], dengue fever [ 75 ], West Nile virus [ 69 ], and communicable disease [ 70 ]. In these interventions, GIS contributed to assessing visit rates for common illnesses in a defined community and identified spatial variability over time [ 71 ]; provided an effective and efficient operational tool for rapidly defining spatial distribution of malaria [ 77 ]; provided a useful tool to track trends in HIV incidence, HIV prevalence, and related risk behavior in a vulnerable population of women [ 72 ]. In addition, GIS provided a tool for analyzing risk factors that increase HIV infections [ 78 ], to accurately identify areas with high incidences of mosquito infestation and interpret the spatial relationship of these areas with potential larval development sites, such as garbage piles and large pools of standing water [ 75 ].…”
Section: Resultsmentioning
confidence: 99%